Hubungan Antara Sense Of Humor Dan Intimate Friendship - Riska, Novia; Widyastuti, Ami (Psikoislamedia: Jurnal Psikologi, 2019)
Humans as social beings cannot escape from others. This makes humans need to interact with people around. One form of interaction is by making friends. Friendship is considered related to mutual understanding and sharing of thoughts, feelings and other secrets. One factor that determines the quality of friendships is the closeness or intimacy. Sense of humor is one of the factors that support the formation of closeness. This study aims to determine the relationship between sense of humor with intimate friendship. The research sample was 394 students of UIN Suska Riau, who were determined using proportional nonrandom sampling technique. Measuring instruments use a scale of sense of humor (Thorson & Powell, 1993) and intimate friendship scale (Sharabany, 2008). The research hypothesis is "there is a relationship between sense of humor with intimate friendship". Based on the results of the product moment correlation analysis of Pearson's correlation coefficient (r) of 0.486 and probability (p) of 0.000 at a significance level of 1%, which means the hypothesis is accepted. There is a very significant relationship between sense of humor with intimate friendship. The results also showed that sense of humor and intimate friendship were positively correlated. This indicates that the higher the sense of humor a person has, the higher the friendship intimate. Additional analysis shows that there is no difference in sense of humor based on the sexes of men and women, and there are differences in intimate friendship based on the sexes of men and women